ANALISIS PENDAPATAN DAN RISIKO USAHATANI CABAI MERAH DI KECAMATAN WAY SULAN KABUPATEN LAMPUNG SELATAN - Anugrah, Dian Febriany; Arifin, Bustanul; Suryani, Ani (Lampung University, 2021)
This research aims to assess the income of red chili farming, the amount of risk faced by red chili farmers, and the correlation between risk and income accepted by the red chili farmers. The study was conducted in Way Sulan Sub-district of South Lampung Regency. The total samples were 56 farmers drawn using a simple random sampling method. The data were collected in March - April 2019 using questionnaires. The first aim was analyzed using the revenue-cost ratio (R/C), which is the comparison between total revenue and total cost. The second aim was analyzed by risk analysis using coefficient variation (CV) and the lower limit (L) on five planting seasons. The third aim was analyzed by Product Moment Pearson correlation. This research results showed that the red chili farming income was profitable because of R/C >1. Risk calculation on five planting seasons results showed that the value of CV<0,50 and L>0, meaning that red chili farming was still profitable in any level of risk. There was positive correlation between the amount of risk and income. It means that the higher level of expected income, the higher level of risk received by farmers. Key words: income, red chili, risk